Renal vein to renal collecting system fistula: An extreme complication from central venous thrombosis secondary to indwelling catheter - Aditya Safaya; Alexandra L. Kharazi; Yachao Zhang; Adele Brudnicki; Samir R. Pandya (Elsevier, 2018)
Central venous catheters are routinely used for resuscitation, chemotherapy and nutrition but are not without risk. Central lines are the most common extrinsic cause of venous thrombosis in neonates and infants. We present an ex-36 week 1800g infant baby girl recovering after a staged repair of gastroschisis with ileostomy and mucous fistula formation. The patient was receiving parenteral nutrition through an indwelling saphenous vein tunneled catheter, with its tip in the inferior vena cava. The patient developed polyuria, with a characteristic odor of the parenteral nutrition and a urine analysis showed glucose and triglyceride levels consistent with the composition of the parenteral nutrition fluid. A fluoroscopic cysto-urogram and an inferior vena-cavogram showed a catheter-associated inferior vena cava thrombosis leading to backpressure changes, diverting all intravenous contrast into the right renal vein and to renal collecting system, thus elucidating the route of the parenteral nutrition fluid reaching the bladder. Our case represents an extreme case of complicated central venous thrombosis. We emphasize the importance of practicing a high index of suspicion for thrombotic complications in severely ill neonates with central venous access. An early diagnosis and aggressive management may prevent progression of the disease towards an overwhelming complication. Keywords: Central venous catheterization complications, Renal vein-collecting system connection, Renal vein- collecting system fistula